THE PROBLEM METHOD IN THE BEGINNING COURSE. - Schmidt, L. A. (The Accounting Review, 1928)
Abstract Many teachers of accounting feel that the present methods of instruction in their field leave much to be desired. Apparently, the necessity of keeping the content of the curriculum up with the rapid expansion of accounting theory and practice has resulted in less attention to the more purely pedagogic aspects of accepted fundamentals than is desirable. The well-nigh universal acceptance of some variation of the balance sheet approach was an inevitable step in the right direction. Insofar as it gets away from the older apprentice methods of doing without understanding and emphasizes methods of logical presentation it is pedagogically sound. But insofar as it leads toward new methods of understanding without doing it is pedagogically fallacious. It is the author's observation that very few accounting students retain the gist of lecture, reading, or discussion unless the subject matter thereof is also embraced in concrete problems worked by the student. Even careful illustrations in the lecture or reading are apparently of little avail unless immediately backed up by concrete problems worked by the student.